Microbial study of organisms isolated from nutritional fruit juices surrounded by local fruit market in Nanded, Maharashtra, India - Ashwini Deshmukh; Mujahed Siddiqui; Umar Khan Pathan; Umesh Dhuldhaj (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Deshmukh AS, Siddiqui MM, Pathan UK, Dhuldhaj UP. 2020. Microbial study of organisms isolated from nutritional fruit juices surrounded by local fruit market in Nanded, Maharashtra, India. Biodiversitas 21: 4240-4246. Growing populations depend on the various food products for their nutritional values, but the hidden hunger for nutrients and vitamins are fulfilled by the fruits and their juices. Fruit juices are one of the most dependable food products, available in the Indian markets. But, standard and quality of juices always matters, hence most suggested one are freshly prepared juices as processed and packed one are mostly contains artificial flavors and food additives in the form of preservatives. Even these freshly prepared juices by local staler are also not free from contaminations. Hence, in this study we focus on the quality of fruit juices sold by the local seller. For this purpose, we collected 5 samples of fruit juices from the premises of Swami Ramanand Teerth Marathwada University, Nanded. The fruit juices are on orange, chiku, banana, apple and grapes. These samples were maintained in the basal media nutrient broth and uniculture of bacteria were isolated and maintained in the slant agar for further experiments. Total microbial load was calculated from collected and it was found that these juice samples contain significant bacterial load (2.5 x 106cfu/mL) that can cause diseases. In further investigations and identifications through the biochemical tests, we found that these juices contaminated with coliforms like E. coli and Klebsiella, along with this we also detected the presence of Listeria spp and Staphylococcus in juices samples.